Weak Markets, Strong Teachers: Recession at Career Start and Teacher Effectiveness - Nagler, Markus; Piopiunik, Marc; West, Martin R. (Journal of Labor Economics, 2020)
How do alternative job opportunities affect teacher quality? We provide causal evidence on this question by exploiting business cycle conditions at career start as a source of exogenous variation in the outside options of potential teachers. Unlike prior research, we directly assess teacher quality with value-added measures of impacts on student test scores, using administrative data on over 30,000 Florida public school teachers. Consistent with a Roy model of occupational choice, teachers entering the profession during recessions are significantly more effective in raising student test scores. Results are supported by robustness tests and unlikely to be driven by differential attrition.